Pengaruh Kepemilikan Manajerial, Kepemilikan Pemerintah, Konsentrasi Kepemilikan, Ukuran Pemerintah, Daya Saing Industri, serta Profitabilitas Perusahaan terhadap Luas Pengungkapan Corporate Social Responsibility - Zulfikar Rizky; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2015)
This study examines the influence of ownership structure by-ownership concentration, director ownership, and government ownership- on Corporate Social Responsibility (CSR) and the association between firm characteristics by-Market Capitalization, Profitability, and degree of industry competitiveness- and the extent of CSR. This study uses Bursa Efek Indonesia(BEI)- listed-firms as sample selected based on purposive sampling method with total 80 firms selected. This study uses a CSR disclosure checklist to measure the extent of CSR disclosure in annual report and a multiple regression analysis to examine the influence of each independent variables on dependent variable.The result shows that ownership concentration has negative influence, and government ownership has positive influence on the extent of CSR on annual report. For the firm characteristics this study finds Market Capitalization and degree of indutry competitiveness have positive influences on the extent of CSR on annual report.